2017
DOI: 10.2217/nnm-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodenticity to Enhance Relaxivity of gadolinium-DTPA Within Crosslinked Hyaluronic Acid Nanoparticles

Abstract: Hydrodenticity explains the boosting (12-times) of the Gd-DTPA relaxivity by tuning hydrogel structural parameters, potentially enabling the reduction of the administration dosage as approved for clinical use. [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…Additionally, Russo et al demonstrated that when Gd-DTPA is encapsulated in polymeric networks, a complex equilibrium is formed by elastic stretches of polymer chains, water osmotic pressure and the hydration degree of Gd-CAs and that this equilibrium is able to boost the relaxivity of Gd-based Contrast Agents. This effect is called Hydrodenticity 58 . The ability of the Hydrodenticity to boost the relaxometric properties of Gd-chelates can, on one side, improve MRI performance and, on the other side, potentially reduce the administered dose of CAs keeping performances unmodified.…”
mentioning
confidence: 99%
“…Additionally, Russo et al demonstrated that when Gd-DTPA is encapsulated in polymeric networks, a complex equilibrium is formed by elastic stretches of polymer chains, water osmotic pressure and the hydration degree of Gd-CAs and that this equilibrium is able to boost the relaxivity of Gd-based Contrast Agents. This effect is called Hydrodenticity 58 . The ability of the Hydrodenticity to boost the relaxometric properties of Gd-chelates can, on one side, improve MRI performance and, on the other side, potentially reduce the administered dose of CAs keeping performances unmodified.…”
mentioning
confidence: 99%
“…Indeed, hydrogel matrices made up of hydrophilic polymers are able to accumulate a large amount of water inside the structure, increasing interactions between water molecules and the metal chelate and, consequently, promoting a relaxivity boosting of the T1 CAs [ 25 , 26 , 28 30 ]. The effect has been very well described by Russo et al in the Hydrodenticity concept [ 31 ]. They synthesized crosslinked Hyaluronic Acid NPs (cHANPs) loaded with Gd-DTPA through a microfluidic flow-focusing process, demonstrating the possibility to improve relaxivity through the tunability of crosslink density, mesh size, hydrophilicity, and loading capability and by changing the process parameters [ 30 ].…”
Section: Gadolinium-based Casmentioning
confidence: 80%
“…Recent examples have proved that it is possible to entrap Gd-based CAs within nanostructures to improve relaxivity without metal complex chemical modification [ 22 31 ]. In some cases, as a result of this “peculiar” encapsulation of the CAs, it has also been reported that the characteristic correlation times, as described by the SBM theory, can be strongly modified.…”
Section: Gadolinium-based Casmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Netti and Torino's group, from the Centre for Advanced Biomaterials for Healthcare, Italian Institute of technology, Napoli, presented a number of studies expected to make clinical impact in the near future. In this special issue, Russo et al describe the effect of hydration of the hydrogel structure/biopolymer matrices, termed 'Hydrodenticity' to improve the relaxometric properties of Gd-DTPA contrast agents used in MRI [5]. In another paper, Russo et hyaluronic acid nanoparticles for theranostic applications [6].…”
mentioning
confidence: 99%